(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2011)
In the conventional design process, the applied methodology is directly related to the designer’s experience and the constraints of the project itself; it is a methodology based on test-error, that could become expensive; it is basically based on decisions taken according to the criteria of the designer, who usually defines what should be modified: material, geometry, dimensions, until reaching the final design that not always has into account analysis for optimization that allows for a better design. In the practice of mechanical design, several aspects are analyzed such as shape, dimensions and topology, and the demand for products encourage the designer to search for new methods and tools in order to optimize the resulting product: elements, machines and structures. At present, this has been posible thanks to the development of computational tools, topology optimization and the finite element method, among others. This work is aimed to illustrate the finite element method to carry out optimization of the topology through the software Ansys for two simple problems: the first one is the optimization of the dimensions of the section of a simple joist and the second one is a problem about shape optimization.